(untitled) (Research, Society and Development, 2021)
Cystic fibrosis (CF) is a rare disease that manifests itself in childhood or adolescence, it is highly lethal and multisystemic, generated through the mutation in the gene that encodes the Cystic Fibrosis Transmembrane Conductance Regulatory Protein, which causes increased viscosity mucus in the human body and forms of diagnosis are required to define the treatment to be followed. The objective of this study was to verify the history of cystic fibrosis and to identify some of the main methods of diagnosis of this pathology. It is an integrative literature review, carried out in the Scientific Electronic Electronic Library Online (SciELO), Medical Literature Analysis and Retrieval databases System Online (MedLine / PUBMED) and Latin American and Caribbean Literature in Health Sciences (LILACS), using the descriptors in DeCS: Cystic Fibrosis, diagnosis, history, using the Boolean AND operator. The selection followed criteria for inclusion and exclusion of articles available completely and free of charge, between the years 2015 and 2020, in Portuguese, English and Spanish. Inconclusive, repetitive studies and integrative reviews were excluded during collection for the research in question. About 459 studies related to cystic fibrosis were found, of which 26 articles met the previously determined criteria and were included in the review. According to the diagnostic methods found, the gold standard is the Sweat Test. Cystic fibrosis is an urgent and chronic disease that causes victims worldwide and that needs early diagnosis in order to increase patient survival.